MODERNIZATION OF THE ORGANIZATIONAL STRUCTURE MANAGEMENT OF ENTERPRISES OF AGRO-INDUSTRIAL COMPLEX - Moldakenova, E.K.; Auezova, K.T.; Amrenova , G.K. (Academic Journal of Physical and Chemical Sciences, 2018)
According to the authors' research, the basis for improving the organizational structure of the management of an agro-industrial enterprise is the identification of the functional significance of an agricultural enterprise. As a result of the formation of a new organizational structure for managing the agro-industrial enterprise, the efficiency of the enterprise will increase. Modernization of the organizational structure of management will contribute to the achievement and maintenance of the agro-industrial enterprise competitiveness in the short term, but in the long term, the development of basic and new key competencies will be required. Why do we need financial government support for agriculture? National holding "KazAgro" acts as an infrastructure investor and source of financing for agricultural producers, necessary for the development of the agricultural sector of the country. However, state subsidies in the field of agriculture and agribusiness should be directed to the creation and promotion of the introduction of advanced technologies for the intensification of production and the modernization of the organizational structure of management.